Actividad anti-inflamatoria de compuestos sesquiterpénicos aislados de Psacalium decompositum (Gray) Rob. & Brett. en modelo de TPA y en la línea celular de macrófagos RAW 264.7 - Mora Ramiro, Beatriz (Universidad Autónoma Metropolitana, 2016)
Inflammation is an adaptative response, triggered by various harmful stimuli, its aim is to eliminate injurious agents, as well as the restoration and normal functioning of the affected tissue or organ. However, this response can be altered and produce permanent damage, which often have pathological consequences, like cardiovascular, respiratory, digestive or autoimune diseases. For this reason, there is a large number of anti-inflammatory drugs nowadays, such as esteroideal and non-steroideal drugs, they have pharmacological action mainly by blocking initiation and amplification mediators of the inflammatory response. It has been reported, nevertheless, that the consumption of anti-inflammatory drugs for long periods may cause adverse effects, which brings us to the pursuit of new anti-inflammatory compounds. Mexico is a country with a very large variety of plant species with diverse medicinal uses, an example of this is Psacalium decompositum, a plant with diverse uses in traditional medicine, among which its antidiabetical and anti-inflammatory properties stand out. Among the main compounds that have been identified in P. decompositum, are cacalol and a rich in fructooligosaccharides (FOS) fraction. It remains unknown if this compounds are responsible for anti-inflammatory action.Objective. Determine the anti-inflammatory activity of the cacalol, cacalol acetate and the fraction rich in fructooligosaccharides of Psacalium decompositum in RAW 264.7 macrophages. Materials and methods. For the in vivo model, male mice of the CD-1 strain were used to induce topical inflammation by the administration of TPA (2.5 μg) in the ear and subsequently the compounds cacalol, cacalol acetate and the fraction FOS as well as the hexanic extract and the aqueous extract (1 μg/ear). For the in vitro study, RAW 264.7 macrophages were cultured and stimulated with LPS (5 μg/mL) to induce an inflammatory response an inflammatory response and subsequently treated at different times (15, 30, 60, 90 and 240 minutes) with the compounds cacalol (100 µM), cacalol acetate (100 µM), the FOS fraction (1µg/mL) and the aqueous extract (10 μg/mL), using dexamethasone as positive control (50 µM). After the treatments, the expression of the TNF- α, IL-6, IL-1β, IL-10 and COX.2 mRNAs was assessed by qPCR, cytokine concentrations (TNF-α, IL-6, IL-1β, IL-10) were measured in the culture medium by the ELISA method and phosphorylation of p65 subunit of NF-κB by the ELISA method. Results. The results showed that both cacalol and cacalol acetate significantly inhibited the development of ear edema by up to 40% compared to the control (only treated with vehicle), unlike the hexanic extract that inhibited 39.2% and the FOS fraction which only inhibited it by 28%. Furthermore, in RAW 264.7 macrophages the compounds significantly decreased the expression of TNF-α, IL-6 and IL-1β, as well as their concentrations in the culture medium. No changes were detected in the expression or concentration of IL-10. The concentrations of the phosphorylated p65 subunit decreased with the extracts and with the isolated compounds.Conclusion. Cacalol, cacalol acetate, as well as the FOS fraction and hexane and aqueous extract, reduce inflammation through the modulation of inflammatory cytokines, suppressing the pro-inflammatory ones; however, they do not modify anti-inflammatory citokines. This effects could be involved in the inhibition of the NF-κB pathway as it decreases the level of the phosphorylated p65 subunit. Even so, it is necessary to continue the study with the transcription factors involved in the regulation of these cytokines.; La inflamación es una repuesta adaptativa que se desencadena por diversos estímulos nocivos y cuyo objetivo es la eliminación de un agente dañino, así como el restablecimiento y funcionamiento normal del tejido u órgano afectado. Esta respuesta puede alterarse produciendo daño permanente y consecuencias patológicas asociadas con enfermedades cardiovasculares, respiratorias, digestivas o autoinmunes. Hoy en día existe un gran número de fármacos antiinflamatorios, esteroideos y no esteroideos, los cuales ejercen su acción farmacológica mediante el bloqueo de moléculas mediadoras de la iniciación y amplificación de la respuesta inflamatoria. Sin embargo, se ha reportado que, independientemente de la naturaleza esteroidea o no esteroidea de los fármacos antiinflamatorios, cuando se consumen por periodos largos pueden generar efectos adversos, lo cual justifica la búsqueda de nuevos compuestos antiinflamatorios. México cuenta con gran variedad de especies vegetales con diferentes usos medicinales. Psacalium decompositum se usa en la medicina tradicional como antidiabética y antiinflamatoria. Entre los principales compuestos identificados en P. decompositum se encuentran el cacalol y una fracción rica en fructooligosacáridos (FOS), los cuales se han reportado con actividad antinflamatoria en modelos de inflamación aguda y en modelo de síndrome metabólico respectivamente. Sin embargo, se desconoce el mecanismo por el cual estos compuestos ejercen su acción antiinflamatoria.Objetivo. Determinar la actividad antiinflamatoria del cacalol, acetato de cacalol y la fracción rica en fructooligosacáridos de Psacalium decompositum en macrófagos RAW 264.7. Materiales y métodos. Para el modelo in vivo se utilizaron ratones machos de la cepa CD-1, a los que se les indujo inflamación tópica mediante la administración de TPA (2.5 µg) en la oreja; posteriormente se administraron los compuestos cacalol, acetato de cacalol y la fracción FOS, así como el extracto hexánico y el extracto acuoso (1 µg/oreja). Para el estudio in vitro se cultivaron macrófagos de la línea RAW 264.7, los cuales fueron estimulados con LPS (5 µg/mL) para inducir una respuesta inflamatoria; posteriormente se trataron por diferentes tiempos (15, 30, 60, 90 y 240 minutos), con los compuestos cacalol (100 µM), acetato de cacalol (100 µM) y la fracción FOS (1 µg/mL), así como el extracto hexánico (10 µg/mL) y el extracto acuoso (10 µg/mL), utilizando como control positivo dexametasona (50 µM). Al final de los tratamientos la expresión del ARNm de TNF-α, IL-6, IL-1β, IL-10 y COX-2 se midió por qPCR; las concentraciones de las citocinas TNF- α, IL-6, IL-1β e IL-10 en el medio de cultivo y la fosforilación de la subunidad p65 de NF-κB se determinaron por el método de ELISA. Resultados. Los resultados mostraron que tanto el cacalol como su acetato inhibieron significativamente el desarrollo del edema auricular en un 40% con respecto al control (vehículo), el extracto hexánico lo inhibió en un 39.2% y la fracción FOS en un 28%. En macrófagos RAW 264.7 los compuestos disminuyeron significativamente la expresión de TNF-α, IL-6 e IL-1β, así como sus concentraciones en el cultivo. No se detectaron cambios en la expresión ni en la concentración de IL-10. La concentración de la subunidad p65 fosforilada disminuyó con los extractos y con los compuestos aislados. Conclusión. El cacalol, el acetato de cacalol, la fracción FOS y los extracto hexánico y acuoso redujeron la inflamación y suprimieron las concentraciones de citocinas proinflamatorias, sin afectar las antiinflamatorias, lo cual podría estar relacionado con inhibición de la vía NF-κB, ya que los nivel de la subunidad de p65 fosforilada fueron reducidos. Es necesario continuar el estudio de losfactores de transcripción implicados en la regulación de dichas citocinas.